2006
DOI: 10.1007/s00432-006-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment of larynx and hypopharynx carcinomas on serum syndecan-1 concentrations

Abstract: These findings suggest that a part of S-syndecan-1 originates from the cancerous tissue, and that S-syndecan-1 levels generally decrease following successful cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Soluble Sdc-1 is present at low levels in the serum of healthy people, but elevated Sdc-1 levels have been reported in cancer patients (Joensuu et al , 2002; Anttonen et al , 2003, 2006; Yang et al , 2007). In our study, we simultaneously examined Sdc-1 and MMP-7 serum levels in colorectal cancer patients and in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soluble Sdc-1 is present at low levels in the serum of healthy people, but elevated Sdc-1 levels have been reported in cancer patients (Joensuu et al , 2002; Anttonen et al , 2003, 2006; Yang et al , 2007). In our study, we simultaneously examined Sdc-1 and MMP-7 serum levels in colorectal cancer patients and in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that Sdc-1 shedding from the membrane of pancreatic, lung and larynx tumour cells is accelerated in comparison with shedding from the membrane of normal cells (Joensuu et al , 2002; Anttonen et al , 2003, 2006). In addition, high pretreatment Sdc-1 serum levels are associated with poor prognosis in lung cancer (small cell and non-small cell carcinoma) treated with platinum-based chemotherapy (Joensuu et al , 2002; Anttonen et al , 2003).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, low serum syndecan-1 level can predict sensitivity to anticancer therapy in larynx and hypopharynx cancer, whereas high posttreatment level is an indicator of relapse [61]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since both these tissues are highly vascularized, cancers here are usually secondary metastases [99]. For lung cancer patients, serum Sdc-1 (S-Sdc-1) levels decline following tumor resection; whereas recurrent lung cancers demonstrate elevated S-Sdc-1 levels [100]. High S-Sdc-1 levels probably indicate high Hpa activity and extensive paracrine growth and proliferation signals.…”
Section: Roles Of Hs and Important Hs-protein Interactions In Cancermentioning
confidence: 99%